Base line sister chromatid exchange frequency in Bos indicus and Bos taurus x Bos indicus crosses - MURALI, N; KANDASAMY, N; PANNEERSELVAM, S (The Indian Journal of Animal Sciences, 2011)
Blood samples were collected from indigenous (Kangayam and Red Sindhi; both Bos indicus) and crossbred (JerseyxRed Sindhi (Ft ) and FriesianxRed Sindhi (F1) crosses: both Bos taurusxBos indicus crosses] cattle reared under similar environmental conditions to collect the information on base line sister chromatid exchange (SeE) frequency. Leucocyte cultures were set with the incorporation of BrdU (1OJlg per ml) after 24h and the sister chromatid differential staining of the slides revealed SeEs. The base line SCE frequencies were not normally distributed in all the 4 genetic groups; but follovved Poisson distribution in Red Sindhi and FriesianxRed Sindhi (F1) crosses. Significant differences were observed between Kangayam and FriesianxRed Sindhi cross, and Red Sindhi and FriesianxRed Sindhi cross. Reasons for the breed differences could not be elucidated, but the differencs in base line SC frequency may reflect differing DNA repairing efficiencies. Â